Patient and physician views on the quality of care in inflammatory bowel disease: Results from SOLUTION-1, a prospective IG-IBD study. (1st December 2014) - Bortoli, Aurora; Daperno, Marco; Kohn, Anna; Politi, Patrizia; Marconi, Stefano; Monterubbianesi, Rita; Castiglione, Fabiana; Corbellini, Ada; Merli, Manuela; Casella, Giovanni; D'Incà, Renata; Orlando, Ambrogio; et al.
Abstract: Introduction: Remarkable differences in quality of care (QoC) might be observed in different countries, affecting quality of life of inflammatory bowel disease (IBD) patients. The aim of this study was to assess patient and physician perceptions of the QoC in Italy. Methods: A multicentre observational study on the quality of care in IBD (SOLUTION-1) was conducted in 36 IG-IBD (Italian Group for Inflammatory Bowel Disease) centres in Italy. The QUOTE-IBD (Quality of Care Through the Patient's Eyes) questionnaire was administered to IBD patients and to the attending physicians. The Quality Impact (QI) score summarises the QUOTE-IBD questionnaire, and a QI > 9 is considered satisfactory. Results: Nine-hundred-ninety-two patients and 75 physicians completed the QUOTE-IBD questionnaire. The patients scored the domains of competence (9.47 vs. 8.55) and costs (9.54 vs. 8.26) higher that the physicians, while information (9.31 vs. 9.43) and continuity of care (8.40 vs. 9.01) were scored lower. The QI score was rated worse by physicians with less experience (< 12 years) with regard to competence (8.0 vs. 9.01), courtesy (8.12 vs. 10.0) and autonomy (8.97 vs. 10.0). Physicians considered the cost domain unsatisfactory. Conclusions: Healthcare was rated as satisfactory overall for Italian patients and physicians. The physicians underestimate their competence and consider the cost of medical management unsatisfactory. The patients are more critical regarding the continuity of care and information. Country-specific data on QoC allow local governments to allocate resources more effectively.